The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.clinph.2017.07.398
|View full text |Cite
|
Sign up to set email alerts
|

Reduced functional connectivity between ventromedial prefrontal cortex and insula relates to longer corrected QT interval in HIV+ and HIV− individuals

Abstract: Objective Prolongation of the QT interval, i.e., measure of the time between the start of the Q wave and the end of the T wave, is a precursor to fatal cardiac arrhythmias commonly observed in individuals infected with the Human Immunodeficiency Virus (HIV), and is related to dysregulation of the autonomic nervous system. We investigated the relationship between QT interval length and resting state functional connectivity (rsFC) of the ventromedial prefrontal cortex (VMPFC), a core region of the brain that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…A number of regions, including left opercular part of inferior frontal gyrus (pars opercularis), superior temporal gyrus, postcentral gyrus, pericalcarine cortex, right insula, and parahippocampal gyrus showed significant differences only in recurrent connections strength w . Some of these, such as the insula and parahippocampal gyrus have been shown to have reduced regional volume and FC in the HIV‐infected population (Kallianpur et al, 2012; McIntosh et al, 2017; Samboju et al, 2018). The balanced integration of excitatory and inhibitory synaptic currents in the local cortex allows the cortical network to operate at high efficiency of information transmission at a low energy cost (Yu, Shen, Wang, & Yu, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of regions, including left opercular part of inferior frontal gyrus (pars opercularis), superior temporal gyrus, postcentral gyrus, pericalcarine cortex, right insula, and parahippocampal gyrus showed significant differences only in recurrent connections strength w . Some of these, such as the insula and parahippocampal gyrus have been shown to have reduced regional volume and FC in the HIV‐infected population (Kallianpur et al, 2012; McIntosh et al, 2017; Samboju et al, 2018). The balanced integration of excitatory and inhibitory synaptic currents in the local cortex allows the cortical network to operate at high efficiency of information transmission at a low energy cost (Yu, Shen, Wang, & Yu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The lingual gyrus (part of the visual processing system) has also been previously reported to be affected in perinatally HIV-infected youths (Sarma et al, 2019). Ances et al (2009) shown to have reduced regional volume and FC in the HIV-infected population (Kallianpur et al, 2012;McIntosh et al, 2017;Samboju et al, 2018). The balanced integration of excitatory and inhibitory synaptic currents in the local cortex allows the cortical network to operate at high efficiency of information transmission at a low energy cost (Yu, Shen, Wang, & Yu, 2018).…”
Section: Rmfm Revealed Disruption Of Local Dynamics Changes Due To mentioning
confidence: 99%
“…They have mentioned that the stimulation of the posterior insular cortex induced increasing degrees of atrioventricular block producing escape rhythms, premature ventricular contractions, QT prolongation, and ultimately death in asystole. More importantly, McIntosh et al [17] showed that QTc prolongation had an important association with distinct patterns of ventromedial prefrontal cortex state functional connectivity (rsFC) with the posterior and anterior insula. Longer QTc and lower CD4 count corresponded to weaker ventromedial prefrontal cortex connectivity with the dorsal striatum in patients with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A number of regions, including left opercular part of inferior frontal gyrus (pars opercularis), superior temporal gyrus, postcentral gyrus, pericalcarine cortex, right insula, and parahippocampal gyrus showed significant differences only in recurrent connections strength w. Some of these, such as the insula and parahippocampal gyrus have been shown to have reduced regional volume and functional connectivity in the HIV-infected population (Kallianpur et al, 2012; McIntosh et al, 2017; Samboju, Philippi, Chan, Cobigo, Fletcher, Robb, Hellmuth, Benjapornpong, Dumrongpisutikul, Pothisri, Paul, Ananworanich, Spudich, Valcour, RV254, et al, 2018). The balanced integration of excitatory and inhibitory synaptic currents in the local cortex allows the cortical network to operate at high efficiency of information transmission at a low energy cost (Yu, Shen, Wang, & Yu, 2018).…”
Section: Discussionmentioning
confidence: 99%